Medication management and logistics amid the COVID-19 pandemic: a systematic review (Research, Society and Development, 2022)
Introduction: The COVID-19 pandemic has changed the global reality, in this new context health systems have undergone several modifications, and the pharmacist is a great ally, assisting in the management and logistics of medicines essential to the treatment of the virus. Objective: To characterize the intrinsic aspects of drug management and logistics during the COVID-19 pandemic. Methods: As a methodology adopted in this systematic review, the prism method was followed, where in the VHL, PubMed and Scielo databases searches were conducted from February to October 2022, using the descriptors: "Hospital Purchase", "COVID-19", "Hospital Inventory Management", "Pharmaceutical Inputs", "Medicines", "Pandemic", "Pharmaceutical Professional" and "National Policy of Pharmaceutical Care". Thus, this research uses the bibliographies of qualitative content, through the exploratory method to describe the data addressed. Results: Ten reports were recorded that met all established parameters and were selected for analysis in this systematic review that take into account the logistics and management of medicines in the period of the COVID-19 pandemic, demonstrating the drastic increase in dispensation and how management can occur bringing the benefits to the patient's health and hospital structure,  highlighted with the performance of the pharmaceutical professional. Conclusions: Pharmaceutical Care is an essential part of patient care in hospitals or pharmacies. During the SARS-CoV-2 pandemic, the role of the pharmacist became of great indispensability, acting in decision-making, monitoring and pharmacovigilance in addition to inventory management in hospital centers, assisting in coping with the virus.